Orthogonal navigation of multiple visible-light-driven artificial microswimmers - Jing Zheng (Nature Portfolio, 2017)
The ability to direct microwimmers along a particular trajectory is advantageous for targeted drug delivery and manufacturing at the microscale. Here Zheng et al. use different types of light-absorbing dyes to enable selective activation of different microswimmers independently from each other.